2021
DOI: 10.3390/atmos12101267
|View full text |Cite
|
Sign up to set email alerts
|

Air Flow Experiments on a Train Carriage—Towards Understanding the Risk of Airborne Transmission

Abstract: A series of experiments was undertaken on an intercity train carriage aimed at providing a “proof of concept” for three methods in improving our understanding of airflow behaviour and the accompanied dispersion of exhaled droplets. The methods used included the following: measuring CO2 concentrations as a proxy for exhaled breath, measuring the concentrations of different size fractions of aerosol particles released from a nebuliser, and visualising the flow patterns at cross-sections of the carriage by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…The ventilation of the Class 802 is similar to other rail stock; therefore, the results described here can be translated to other types of modern long‐distance train carriages. A series of CO 2 experiments were conducted by Woodward et al, 21 which will be used to compare and verify the models in Section 4.…”
Section: Carriage Geometry and Mechanical Ventilationmentioning
confidence: 99%
See 3 more Smart Citations
“…The ventilation of the Class 802 is similar to other rail stock; therefore, the results described here can be translated to other types of modern long‐distance train carriages. A series of CO 2 experiments were conducted by Woodward et al, 21 which will be used to compare and verify the models in Section 4.…”
Section: Carriage Geometry and Mechanical Ventilationmentioning
confidence: 99%
“…The 1D‐model requires estimates for the longitudinal flowrate and the turbulent diffusion coefficient, which are not necessarily known a priori. To estimate these parameters, we will compare the 1D‐model with CO 2 measurements conducted in a train carriage by Woodward et al 21 in August 2020. These measurements used passengers as sources of CO 2 .…”
Section: Comparison Between Models and Co2 Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many countries are making high economic investments to equip schools with CO 2 meters [ 41 , 42 ]. In addition, other isolated initiatives have successfully implemented this methodology in shopping centers [ 43 ], collective transport [ 44 , 45 , 46 ], offices [ 47 ], or university and school classrooms [ 47 , 48 , 49 , 50 , 51 , 52 ]. Specifically, a recent study in Italy reported an 82% reduction in secondary COVID-19 infections in schools where they controlled air renewal from CO 2 measurements [ 53 ].…”
Section: Introductionmentioning
confidence: 99%